2014
DOI: 10.1039/c4ta00239c
|View full text |Cite
|
Sign up to set email alerts
|

A maize-like FePO4@MCNT nanowire composite for sodium-ion batteries via a microemulsion technique

Abstract: A maize-like FePO4@MCNT composite was prepared through non-covalent surface treatment and used as a cathode for sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 55 publications
(59 reference statements)
0
30
0
Order By: Relevance
“…Since high temperature calcination leads to the crystallization of amorphous FePO 4 , carbon decoration should be conducted at low temperatures. Various carbon materials, such as carbon nanotube, graphene, carbonized polyaniline, and Kejen Black, have been reported to improve the sodium storage performance of amorphous FePO 4 . For example, Fang et al designed a mesoporous amorphous FePO 4 embedded in carbon matrix ( Figure a), which delivered a high reversible capacity of 151 mAh g −1 with a stable cyclability with 94% capacity retention over 160 cycles (Figure c,d) .…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Since high temperature calcination leads to the crystallization of amorphous FePO 4 , carbon decoration should be conducted at low temperatures. Various carbon materials, such as carbon nanotube, graphene, carbonized polyaniline, and Kejen Black, have been reported to improve the sodium storage performance of amorphous FePO 4 . For example, Fang et al designed a mesoporous amorphous FePO 4 embedded in carbon matrix ( Figure a), which delivered a high reversible capacity of 151 mAh g −1 with a stable cyclability with 94% capacity retention over 160 cycles (Figure c,d) .…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Fang et al used a simple chemically induced precipitation method to successfully prepare mesoporous amorphous FePO 4 /C nanospheres (Figure B), exhibiting a high initial discharging capacity of 151 mA h g −1 at 20 mA g −1 and stable cyclability of 94% capacity retention over 160 cycles (Figure C). In addition, biofacilitated energy‐efficient synthesis methods and microemulsion techniques have also been used to prepare amorphous FePO 4 /C nanocomposites with different morphologies, with encouraging electrochemical performance.…”
Section: Amorphous Cathode Materialsmentioning
confidence: 99%
“…Obviously, the introduction of a highly conductive matrix to form a composite material becomes a logical and reasonable approach to achieve higher electron conductivity. [14][15][16][17][18] For example, Liu et al 10 showed that a mixture of single-walled carbon nanotubes and FePO 4 nanoparticles showed much improved battery performance and high cyclability. single-walled carbon nanotubes are a highly connected network that can facilitate the electron transport of embedded FePO 4 particles.…”
Section: Introductionmentioning
confidence: 99%